Effective Safety Management Using the Implementation of Safety Performance Practises in Construction Project - Asri, Alia Arisha (IRC, 2019)
Today, construction industry is a growing area of Malaysian economy, improving the growth of socio-economic of nation as well as providing the essential infrastructure and improved amenities for social comfort. The construction industry has grown in years and many safety practices that have been applied have helped the industry to further improve in safety performance. The collective impact of implementing several safety practices framework does indeed make a significant impact on safety performance.